An Outbreak of Fatal Bordetella bronchiseptica Bronchopneumonia in Puppies - Chambers, J.K. (J Comp Pathol, 2019)
Twenty-two newborn puppies that did not receive colostrum exhibited acute respiratory signs and died at a breeding facility. Pathological examinations were performed on four of the puppies. At necropsy examination, the lungs were firm and mottled dark red, consistent with acute bronchopneumonia. Histopathologically, there was marked infiltration of neutrophils and macrophages into the bronchi and alveoli, and gram-negative coccobacilli were attached diffusely to the cilia of bronchial mucosa. Immunohistochemistry for Bordetella bronchiseptica antigen revealed positive labelling of the bacterial agents. On electron microscopy, a large number of coccobacilli were observed attaching to the cilia of bronchial epithelial cells. Real-time polymerase chain reaction amplified a B. bronchiseptica gene from the affected lung tissue. Based on these findings, the four puppies were diagnosed with fatal B. bronchiseptica bronchopneumonia.